MANURE USAGE STUDY AND PLANT VEGULATOR COCENTRATION TO PLANT GROWNTH AND FIELD CAULI FLOWER (Brassica oleraccae var botryis L.) - Aris Dedy Joko Sulistyo; Pramono Hadi, Tri Rahayu (PROSEDING, 2022)
The research can be concluded as follows: The best manure for growth and yield of flower cabbage plants is N 3 (quail manure) and the results in the treatment of manure types In the treatment of N (type of manure has aXvery significant effect on plant height, flower weight fresh per planting, diameter of flowers, b closely the fresh vegetativexpart , and b closely the dry vegetative part of the plan , the treatment of growth regulators has a significant effect on the N treatment (type of manure has very significant effect on plant height, fresh flower weight per tanmaan, diamter flowers, b closely vegetative parts fresh, and b closely vegetative part of dry crop . the interaction between treatment concentration liquid organic fertilizer and plant growth regulator no significant effect on all parameters. . combination treatment of N 3 V 3provides the highest weight of fresh flowers 295.33 g ,obtained in combination N 3 V 2 (giving quail manure and tum regulating agent) buh at a concentration of 2 cc / 1 of water. The lowest fresh flower weight per plant was 197.67 g, obtained at a combination of N 1 V 1 treatment (administration of cow manure and growth regulators at a concentration of 1 cc / l water). Keywords: Use of Manure, Concentration of ZPT, Cabbage Flowers